2017
DOI: 10.1002/ijc.30586
|View full text |Cite
|
Sign up to set email alerts
|

Identification and prediction of health‐related quality of life trajectories after a prostate cancer diagnosis

Abstract: The aim of our study was to identify physical and mental health-related quality of life (HRQoL) trajectories after a prostate cancer diagnosis and systematically characterize trajectories by behaviours and prognostic factors. Prostate cancer survivors (n = 817) diagnosed between 1997 and 2000 were recruited between 2000 and 2002 into a prospective repeated measurements study. Behavioural/prognostic data were collected through in-person interviews and questionnaires. HRQoL was collected at three post-diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…However, the direction of the association indicates that people who were more physically active before discharge from rehabilitation were more likely to follow the high HR-QoL trajectory compared to people in the moderate HR-QoL trajectory. This might imply that more physical activity is associated with higher HR-QoL, which supports previous literature [7,9,50,51].…”
Section: Discussionsupporting
confidence: 90%
“…However, the direction of the association indicates that people who were more physically active before discharge from rehabilitation were more likely to follow the high HR-QoL trajectory compared to people in the moderate HR-QoL trajectory. This might imply that more physical activity is associated with higher HR-QoL, which supports previous literature [7,9,50,51].…”
Section: Discussionsupporting
confidence: 90%
“…Health outcomes for PCa are influenced by various physical and psychological factors, such as symptoms experienced [ 10 ], treatment received [ 11 , 12 ], and extent of masculine identity threat [ 13 ]. There is also support for different mental health-related quality of life trajectories [ 14 ]. Combined with methodological differences, these factors may have contributed to variations in reported outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study characterized postdiagnosis trajectories of physical and mental Health-Related Quality of Life (HRQoL) in prostate cancer survivors and identified a group of patients with lower and declining HRQoL for potential interventions. [24] Another study characterized trajectories of physical activity and physical function in cancer survivors enrolled in a randomized trial of home-based lifestyle counseling and identified characteristics of survivors who benefited from the assigned interventions. [25] Cautions and challenges…”
Section: Statistical Methods Of the Trajectory Analysismentioning
confidence: 99%